2003
DOI: 10.1111/j.1365-2621.2003.tb09663.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Affecting the Destruction of Escherichia coli O157:H7 in Apple Cider Treated with Fumaric Acid and Sodium Benzoate

Abstract: Destruction of Escherichia coli O157:H7 in apple cider treated with fumaric acid and sodium benzoate (0.15% and 0.05% w/v, respectively) was determined under pH and storage temperatures that commonly occur in apple cider. At 5 °C storage, while destruction of E. coli O157:H7 in the presence of preservatives increased with time, there was little decline in E. coli O157:H7 populations in the absence of the preservatives. Increasing storage temperatures to 15 Њ Њ Њ Њ ЊC and 25 Њ Њ Њ Њ ЊC significantly increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In addition, other sanitizers such as organic acids have been studied for their effectiveness in improving the microbial safety of foods, and fumaric acid has been used as a food preservative (Liao, Liu, Frear, & Chen, 2008). Fumaric acid is a food-grade acidulant with strong bactericidal activity (Comes & Beelman, 2002), and it has been used as an antimicrobial against pathogenic bacteria in fresh-cut lettuce and apple cider (Chikthimmah, Laborde, & Beelman, 2003;Kondo, Murata, & Isshiki, 2006). Treatment with 50 mM of fumaric acid for 10 min caused a 2-log reduction in populations of E. coli O157:H7 and Salmonella typhimurium attached to fresh-cut lettuce (Kondo et al, 2006), and fumaric acid (10%) had a significant bactericidal effect when added to apple cider (Chikthimmah et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other sanitizers such as organic acids have been studied for their effectiveness in improving the microbial safety of foods, and fumaric acid has been used as a food preservative (Liao, Liu, Frear, & Chen, 2008). Fumaric acid is a food-grade acidulant with strong bactericidal activity (Comes & Beelman, 2002), and it has been used as an antimicrobial against pathogenic bacteria in fresh-cut lettuce and apple cider (Chikthimmah, Laborde, & Beelman, 2003;Kondo, Murata, & Isshiki, 2006). Treatment with 50 mM of fumaric acid for 10 min caused a 2-log reduction in populations of E. coli O157:H7 and Salmonella typhimurium attached to fresh-cut lettuce (Kondo et al, 2006), and fumaric acid (10%) had a significant bactericidal effect when added to apple cider (Chikthimmah et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fumaric acid is a food-grade acidulant with strong bactericidal activity (Comes & Beelman, 2002), and it has been used as an antimicrobial against pathogenic bacteria in fresh-cut lettuce and apple cider (Chikthimmah, Laborde, & Beelman, 2003;Kondo, Murata, & Isshiki, 2006). Treatment with 50 mM of fumaric acid for 10 min caused a 2-log reduction in populations of E. coli O157:H7 and Salmonella typhimurium attached to fresh-cut lettuce (Kondo et al, 2006), and fumaric acid (10%) had a significant bactericidal effect when added to apple cider (Chikthimmah et al, 2003). Although there have been studies of the effect of chemical treatments on inhibiting microorganisms in alfalfa sprouts (Wade et al, 2003) and mung bean sprouts (Jin & Lee, 2007), there are few reports available on broccoli sprouts.…”
Section: Introductionmentioning
confidence: 99%
“…The killing effect in our case was more pronounced at room temperature, this is not unexpected, since metabolism of microorganisms is active at that temperature, whereas at refrigeration temperatures these reactions become slower, therefore growth and death rates are lower. The ability of both survival and growth of E. coli O157:H7 in acidic foods and beverages at different storage temperatures have been documented 14 . Fruits and vegetables can become contaminated with E. coli O157:H7 whilst growth in fi elds or during harvest, handling, washing/cleaning, processing, distribution, retail, preparation and fi nal use 15,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, apple juice leads consumption of all apple products (Table 22.4). Chikthimmah et al (2003) reported a 5-log cycle reduction in Escherichia coli O157:H7 in cider by adding fumaric acid (0.15% w/v) and sodium benzoate (0.05% w/v) to the product. Thus, the apple juice and cider are extracted liquids containing soluble solids primarily fruit sugars and acids.…”
Section: Apple Juice and Cidermentioning
confidence: 99%